2021
DOI: 10.1124/molpharm.121.000262
|View full text |Cite
|
Sign up to set email alerts
|

A Role for VCP/p97 in the Processing of Drug-Stabilized TOP2-DNA Covalent Complexes

Abstract: DNA topoisomerase II (TOP2) poisons induce protein-DNA crosslinks termed TOP2-DNA covalent complexes, in which TOP2 remains covalently bound to each end of an enzymeinduced double strand DNA break (DSB) via a 5'-phosphotyrosyl bond. Repair of the enzyme-induced DSB first requires the removal of the TOP2 protein adduct which, among other mechanisms, can be accomplished through the proteasomal degradation of TOP2.VCP/p97 is a AAA ATPase which utilises energy from ATP hydrolysis to unfold protein substrates, whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 53 publications
1
10
0
Order By: Relevance
“…A key finding in our work is that while MRE11 overexpression can overcome proteasome inhibition, it cannot overcome inhibition of the ATPase/segregase VCP/p97. Recent work has demonstrated that VCP/p97 is important for repairing TOP2-induced damage (Swan et al, 2021), and our results agree with those findings. Interestingly, we found that inhibition of VCP/p97 by NMS873 led to lower levels of TOP2ccs than inhibition of the proteasome using the inhibitor MG132 (Supplementary Figure S3), but that inhibition of VCP/p97 was epistatic to inhibition of the proteasome by MG132.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…A key finding in our work is that while MRE11 overexpression can overcome proteasome inhibition, it cannot overcome inhibition of the ATPase/segregase VCP/p97. Recent work has demonstrated that VCP/p97 is important for repairing TOP2-induced damage (Swan et al, 2021), and our results agree with those findings. Interestingly, we found that inhibition of VCP/p97 by NMS873 led to lower levels of TOP2ccs than inhibition of the proteasome using the inhibitor MG132 (Supplementary Figure S3), but that inhibition of VCP/p97 was epistatic to inhibition of the proteasome by MG132.…”
Section: Discussionsupporting
confidence: 93%
“…MRE11 upregulation fails to overcome VCP/p97 inhibition for TOP2cc processing VCP/p97 is an AAA + protein that enhances proteolysis of selected substrates both from cell membranes and within the nucleus (Meyer and Weihl, 2014). Austin and colleagues recently reported that VCP/p97 inhibition hinders the repair of TOP2ccs (Swan et al, 2021). Similar to their results, we found that the VCP/p97 inhibitor NMS873 (Magnaghi et al, 2013) plus etoposide resulted in elevated levels of TOP2ccs compared to etoposide alone (Supplementary Figures 3A-D).…”
Section: Upregulation Of Mre11 Leads To Processing Of Top2ccs In the ...mentioning
confidence: 99%
“…6a), which partially offset the in uence on replication pressure and DSB formation (Fig. 6b, 6C) (Swan et al, 2021). As time went on, the p97 deletion led to a large number of protein aggregation in the nucleus, and DPC could not be cleared.…”
Section: Discussionmentioning
confidence: 90%
“…1). In this case, the resulting TOP2-DNA covalent complexes are processed through one of a number of pathways to a protein-free state before DNA repair (59)(60)(61)(62). Classically, this occurs when cells are exposed to TOP2 poisons such as etoposide, but the enzyme can also be poisoned when it encounters endogenous DNA damage such as base excision repair (BER) intermediates (63) .…”
Section: Topoisomerases / Top2b and Stimulus-responsive Gene Expressionmentioning
confidence: 99%